2018
DOI: 10.1016/j.flora.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Lack of floristic identity in campos rupestres —A hyperdiverse mosaic of rocky montane savannas in South America

Abstract: of floristic identity in campos rupestres − a hyperdiverse mosaic of rocky montane savannas in South America.Flora http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 41 publications
5
54
0
Order By: Relevance
“…Through the scenarios, protected areas in riverine forest will have more stable climates across the southeastern portion of its current distribution, highlighting the importance of these areas for protecting viable population sizes of riverine species. Congruent with the results for riverine forest, our future scenario models showed that rock outcrop habitats will lose more climatically suitable areas in their lower latitudes, suggesting that southernmost sites may function as climatic refugia for this hyperdiverse habitat (Neves et al, ). However, given the scattered spatial configuration of these rock outcrop sites, dispersal is likely to be very limited, which suggests that conservation strategies might need to consider new protected areas that connect these outcrop islands through the lowlands.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Through the scenarios, protected areas in riverine forest will have more stable climates across the southeastern portion of its current distribution, highlighting the importance of these areas for protecting viable population sizes of riverine species. Congruent with the results for riverine forest, our future scenario models showed that rock outcrop habitats will lose more climatically suitable areas in their lower latitudes, suggesting that southernmost sites may function as climatic refugia for this hyperdiverse habitat (Neves et al, ). However, given the scattered spatial configuration of these rock outcrop sites, dispersal is likely to be very limited, which suggests that conservation strategies might need to consider new protected areas that connect these outcrop islands through the lowlands.…”
Section: Discussionsupporting
confidence: 71%
“…However, given the scattered spatial configuration of these rock outcrop sites, dispersal is likely to be very limited, which suggests that conservation strategies might need to consider new protected areas that connect these outcrop islands through the lowlands. In fact, previous studies (Mews, Pinto, Eisenlohr, & Lenza, ; Neves et al, ) provided evidence that rock outcrop habitats and their surrounding lowland savannas are likely to form a continuous metacommunity with spatial variation in woody plant population sizes being mainly driven by source–sink dynamics (Pulliam & Danielson, ). Therefore, here we stress that protected areas aiming to secure biodiversity of rock outcrop habitats should not be limited to rock outcrop areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environments on rocky outcrops usually possess low floristic diversity compared to their surrounding ecosystems (Rizzini 1997;Jacobi et al 2008;Neves et al 2017). The diversity estimated by the Shannon index for the studied ferruginous rupestrian complex and quartzitic rupestrian complex were lower than that observed in other areas throughout Serra do Espinhaço.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, the few studies that have been do are largely limited to the Quadrilátero Ferrífero (Iron Quadrangle; Jacobi & Carmo 2008a;Vincent & Meguro 2008;Messias et al 2011;. Floristic studies are of great importance for the Serra do Espinhaço given the great beta diversity of its rupestrian complex (Neves et al 2017). Studies of this nature, among other important aspects, permit a better understanding of the geographic distribution of species and the establishment of patterns of endemism, as well as the development of conservation and restoration strategies for degraded areas.…”
Section: Introductionmentioning
confidence: 99%